Impact of maternal social vulnerability and timing of prenatal care on outcome of prenatally detected congenital heart disease. (1st September 2022) - Perez, M. T.; Bucholz, E.; Asimacopoulos, E.; Ferraro, A. M.; Salem, S. M.; Schauer, J.; Holleman, C.; Sekhavat, S.; Tworetzky, W.; Powell, A. J.; Sleeper, L. A.; Beroukhim, R. S.
ABSTRACT: Objectives: Early prenatal detection of congenital heart disease (CHD) allows mothers to plan for their pregnancy and delivery; however, the effect of certain sociodemographic and fetal factors on prenatal care has not been investigated thoroughly. This study evaluated the impact of maternal and fetal characteristics on the timing of prenatal diagnosis of CHD and fetal and postnatal outcomes. Methods: This retrospective multicenter cohort study included women with a fetal echocardiographic diagnosis of CHD between 2010 and 2019. Women were grouped into quartiles of social vulnerability (quartiles 1–4; low–high) using the 2014 social vulnerability index (SVI) provided by the Centers for Disease Control and Prevention. A fetal disease severity score (range, 1–7) was calculated based on a combination of CHD severity (mild = 1; moderate = 2; severe, two ventricles = 3; severe, single ventricle = 4 points) and prenatally diagnosed genetic abnormality, non‐cardiac abnormality and fetal hydrops (1 point each). Late diagnosis was defined as a fetal echocardiographic diagnosis of CHD after 24 weeks' gestation. Univariate and multivariable regression analyses were used to identify factors associated with late diagnosis, termination of pregnancy (TOP), postnatal death, prenatal–postnatal discordance in CHD diagnosis and severity and, for liveborn infants, to identify which prenatal variables were associated with postnatal death or heart transplant. Results: Among 441 pregnancies included, 94 (21%) had a late diagnosis of CHD. Late diagnosis was more common in the most socially vulnerable quartile, 38% of women in this group having diagnosis > 24 weeks, compared with 14–18% in the other three quartile groups. Late diagnosis was also associated with Catholic or other Christian religion vs non‐denominational or other religion and with a lower fetal disease severity score. There were 93 (21%) TOP and 26 (6%) in‐utero fetal demises. Factors associated with TOP included early diagnosis and greater fetal disease severity. Compared with the other quartiles, the most socially vulnerable quartile had a higher incidence of in‐utero fetal demise and a lower incidence of TOP. Among the 322 liveborn infants, 49 (15%) died or underwent heart transplant during the follow‐up period (range, 0–16 months). Factors associated with postnatal death or heart transplant included longer delay between obstetric ultrasound examination at which CHD was first suspected and fetal echocardiogram at which CHD was confirmed and greater fetal disease severity. Conclusions: High social vulnerability, Catholic or other Christian religion and low fetal disease severity are associated with late prenatal CHD diagnosis. Delays in CHD diagnosis are associated with fewer TOPs and worse postnatal outcome. Therefore, efforts to expedite fetal echocardiography following abnormal obstetric screening, particularly for at‐risk women (e.g. those with high SVI), have the potential to impact pregnancy and postnatal outcome among the prenatally diagnosed CHD population. © 2022 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Bebbington. Click here to view the Editorial.